AIAA SPACE 2010 Conference &Amp; Exposition 2010
DOI: 10.2514/6.2010-8797
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Perspectives and Methods for Value-Driven Design

Abstract: Recent years have seen a push to use explicit consideration of "value" in order to drive design. This paper conveys the need to explicitly align perspectives on "value" with the method used to quantify "value." Various concepts of value are introduced in the context of its evolution within economics in order to propose a holistic definition of value. Operationalization of value is discussed, including possible assumption violations in the aerospace domain. A series of prominent Value-Centric Design Methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…MAUT has been incorporated in the multi-attribute trade-space exploration (MATE) paradigm for generating a multitude of system designs and identifying the optimal ones, [118], [119], [120] and [121]. It was also applied in establishing the requirements' specification of commercial aircraft [122], in evaluating space system designs for the telecommunications and deep-space observation missions [103], and the development of satellite value models [123].…”
Section: Multi-attribute Utility Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…MAUT has been incorporated in the multi-attribute trade-space exploration (MATE) paradigm for generating a multitude of system designs and identifying the optimal ones, [118], [119], [120] and [121]. It was also applied in establishing the requirements' specification of commercial aircraft [122], in evaluating space system designs for the telecommunications and deep-space observation missions [103], and the development of satellite value models [123].…”
Section: Multi-attribute Utility Theorymentioning
confidence: 99%
“…This may be more appropriate for the design of civil aviation systems, since profit is the driving factor, while less tangible aspects of value, such as environmental friendliness, customer loyalty and contribution to society, are more difficult to monetise. Ross et al [103], applying a series of Value-Centric Design Methodologies in the evaluation of two case studies, a telecommunication mission and a deep-space observation mission, demonstrated than no method is fully complete in capturing value. Instead, as they point out, the perspectives/perceptions of value need to be aligned with the method selected for pursuing VDD.…”
mentioning
confidence: 99%
“…Multi-attribute utility theory has been used as a standard technique in several applications in research and real-world problems, from the airline industry [7] and earthquake projects [5] to deep-space observation mission [35].…”
Section: Multi-attribute Value and Utility Modellingmentioning
confidence: 99%
“…In this equation, and are the total and individual utility functions respectively, while are the scaling constants and is an additional normalization constant generated through the iterative process presented in Appendix 6B, (Keeney and Raiffa 1976 (Ross et al 2010).…”
Section: Multi-attribute Utility and Value Modellingmentioning
confidence: 99%